Datos sobre Tierra del Fuego - Thomas Bridges (Revista del Museo de La Plata)
With much pleasure in reply to your request I write the following brief & truthful account of Tierra del Fuego hoping thus to interest the general reader, & to help any who may he thinking of seeking a  living there.